The Development of Students Career Aspiration - Mayra, Zara; Sunawan, Sunawan; Purwanto, Edy (Jurnal Bimbingan Konseling, 2020)
The purpose of this study was to describe the pattern of development of aspirations of students of SD, SMP, andSMA. The subject of this study was students of SD, SMP and SMA Semarang with a totalof 300 students selected using cluster random sampling technique. The data collectiontechnique used was CASR (Career Aspiration Scale-Revised) instruments. To answer the problem of the study, mixedmethod research was usedwith a sequential explanatory model design. The data analysis technique was donethrough two stages, namely quantitative data analysis (Cross-SectionalSurvey) with two-way and qualitative data analysis (ANOVA) with ethnographic methods. The results showed that gender did not have a significant effect on the development of student career aspirations, on the other hand, the level of education had a significant effect on the development of student career aspirations, especially in the aspects of Achievement and Leadership. This study provided counselors with an understanding of the career aspirations of the students, andas seen today, the career aspirations formed by students in careerdevelopment is important.